(untitled) (Nexo Revista Científica, 2021)
This study deals with ensuring fire safety in buildings of a cluster animal industrial complex by optimizing legislative measures and analyzing factors that affect the quality and reliability of the results of calculating fire risk. The research involved the following methods: expert assessment; calculating individual fire risk; modeling evacuation of people in the form of an individual flow model of human traffic. The conceptual features of the complex’s buildings required developing the design and technical solutions that would reduce inefficient costs on the one hand, and, on the other, would ensure meeting fire safety requirements. The individual fire risk for employees of the asset to be protected is 2.91 ×10-7 per year-1 (0.291 ×10-6 per year). That is, it does not exceed the characteristic value established by Federal law No. 123-FZ dated 22.07.2008 ’Technical regulations on fire safety’. After the introduction of the fire risk assessment system at the legislative level, the owners of objects have received the opportunity to optimize the cost of fire safety and the required level of human safety.